Carrier-grade NTP clock synchronization scheme of SD-WAN network - Qiangen ZHAO; Yu WANG; Ling TANG; Yongming YAN (Dianxin kexue)
SD-WAN is developing rapidly, and telecom operators and Internet companies are constantly expanding their layout.As a technology with diverse forms, SD-WAN has not made a clear specification for clock synchronization.The importance of clock synchronization to SD-WAN technology implementation and business running was analyzed.The advantages and disadvantages of the clock synchronization scheme of Internet public NTP service widely used in SD-WAN realizations were sketched.Thus the clock synchronization scheme of self-built NTP service in different scenarios was discussed.Furthermore, a clock synchronization method using management tunnel to transmit encrypted NTP synchronization data was designed, which made SD-WAN platform and devices obtain higher security and stability in time synchronization.